Anti‐FcγRIIB (CD32) Antibodies Differentially Modulate Murine FVIII‐Specific Recall Response in vitro. (August 2017) - Vollack, N.; Friese, J.; Bergmann, S.; Cragg, M. S.; Tiede, A.; Werwitzke, S.
Abstract: Fc gamma receptors (Fc γ Rs) for IgG regulate adaptive immune responses by modulating activating and inhibitory signalling pathways within immune cells. Data from a haemophilia A mouse model demonstrate that genetic deletion or blockade of the inhibitory Fc γ R (CD32) suppresses the formation of antibody‐secreting cells (ASCs) in vitro . Mechanisms preventing the FVIII‐specific recall response, however, remain unclear. Here, the potential role of CD32 inhibition was studied by differentially modulating receptor activity with selected anti‐CD32 monoclonal antibodies (mAbs). Splenocytes from immunized FVIII ‐/‐ mice were restimulated with FVIII in the absence or presence of different anti‐CD32 mAbs over 6 days. At day 6, cytokine release was quantified from cell culture supernatant and the formation of FVIII‐specific ASCs assessed. Binding of FVIII‐containing immune complexes (F8‐ICs) to bone marrow‐derived dendritic cells (BMdDCs) was also investigated. The antagonistic CD32 mAb AT128 suppressed the formation of FVIII‐specific ASCs and reduced secretion of IFN‐ γ and IL‐10. In contrast, the agonistic mAbs AT130‐2 and AT130‐5, and their F(ab')2 fragments, allowed the formation of FVIII‐specific ASCs, even though the full IgG of AT130‐2 reduced binding of F8‐ICs to CD32. Data suggest that an inhibitory signal is transmitted when F8‐ICs bind to CD32 and that this signal is required during memory B cell (MBC) activation to support formation of FVIII‐specific ASCs. If the inhibitory signal is lacking due to CD32 deletion or blockade with antagonistic anti‐CD32 mAbs, FVIII‐specific T cell stimulation and ASC formation are suppressed, whereas agonistic stimulation of CD32 restores T cell stimulation and ASC formation.